The Role of Business Analysis in Strategic Planning: Discuss How Business Analysis Contributes to the Strategic Planning Process in Businesses - Mohammed Iberaheem (East Asian Journal of Multidisciplinary Research, 2023)
This research paper aims to discuss the essential role that business analysis plays in strategic planning, primarily by focusing on how it helps organizations to understand their current position, envision potential future scenarios, and determine the best path forward to achieve their business objectives. The methodology of this study hinges on a comprehensive literature review and analysis of existing theories, models, and case studies pertinent to business analysis and strategic planning. The findings showed that organizations incorporating strong business analysis into their strategic planning process are more likely to achieve their objectives and gain a competitive edge. Furthermore, challenges that organizations might face in integrating business analysis with strategic planning and provides insights on how to mitigate them effectively. The paper concludes that business analysis is not merely an optional component but an indispensable aspect of strategic planning.